1992
DOI: 10.1200/jco.1992.10.7.1141
|View full text |Cite
|
Sign up to set email alerts
|

The toxic and hematologic effects of interleukin-1 alpha administered in a phase I trial to patients with advanced malignancies.

Abstract: We conclude that at doses of IL-1 alpha that can be given safely to cancer patients, significant, potentially beneficial hematopoietic effects occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(70 citation statements)
references
References 24 publications
2
67
0
1
Order By: Relevance
“…Clinical trials of cancer patients with IL-1 have been performed before, but only resulted in an antitumor response of o5% to daily bolus IL-1 therapy, mainly due to tachyphylaxis (Smith et al, 1992;Janik et al, 1996). Our observations suggest that combined treatment of IL-1b and IFNg might be more efficient.…”
Section: Discussionmentioning
confidence: 81%
“…Clinical trials of cancer patients with IL-1 have been performed before, but only resulted in an antitumor response of o5% to daily bolus IL-1 therapy, mainly due to tachyphylaxis (Smith et al, 1992;Janik et al, 1996). Our observations suggest that combined treatment of IL-1b and IFNg might be more efficient.…”
Section: Discussionmentioning
confidence: 81%
“…In the Memorial Sloan-Kettering and BRMP studies, significant increases in the platelet counts were observed one to two weeks after treatment, and increased megakaryocytes were also observed in bone marrow biopsies performed after seven days of IL-1 treatment in the IL-1 study at the BRMP. Dose-related increases in serum IL-6 levels also were noted after IL-1 treatment in both studies [16,17].…”
Section: Phase I Trialsmentioning
confidence: 99%
“…Patients experienced a number of flu-like symptoms including chills, rigors, fever, nausea, vomiting, fatigue, headache, myalgia and mild somnolence [16]. Fever, chills and rigors occurred in almost every patient but were not dose-limiting.…”
Section: Phase I Trialsmentioning
confidence: 99%
See 2 more Smart Citations